A commentary on the healthcare transition policy landscape for youth with disabilities or chronic health conditions, the need for an inclusive and equitable approach, and recommendations for change in Canada - Nguyen, Linda; Dawe-McCord, Claire; Frost, Michael; Arafeh, Musa; Chambers, Kyle; Arafeh, Dana; Pozniak, Kinga; Thomson, Donna; Mosel, JoAnne; Cardoso, Roberta; Galuppi, Barb; Strohm, Sonya; et al. (Frontiers in Rehabilitation Sciences, 2023)
There is a growing number of youth with healthcare needs such as disabilities or chronic health conditions who require lifelong care. In Canada, transfer to the adult healthcare system typically occurs at age 18 and is set by policy regardless of whether youth and their families are ready. When the transition to adult services is suboptimal, youth may experience detrimental gaps in healthcare resulting in increased visits to the emergency department and poor healthcare outcomes. Despite the critical need to support youth with disabilities and their families to transition to the adult healthcare system, there is limited legislation to ensure a successful transfer or to mandate transition preparation in Canada.This advocacy and policy planning work was conducted in partnership with the Patient and Family Advisory Council (PFAC) within the CHILD-BRIGHT READYorNot™ Brain-Based Disabilities (BBD) Project and the CHILD-BRIGHT Policy Hub. Together, we identified the need to synthesize and better understand existing policies about transition from pediatric to adult healthcare, and to recommend solutions to improve healthcare access and equity as Canadian youth with disabilities become adults.In this perspective paper, we will report on a dialogue with key informants and make recommendations for change in healthcare transition policies at the healthcare/community, provincial